2019
DOI: 10.1123/ijspp.2018-0645
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Long Sprint Ability–Oriented Small-Sided Games Using Different Ratios of Players to Pitch Area on Internal and External Load in Soccer Players

Abstract: Purpose: To examine the internal and external load imposed by long sprint ability–oriented small-sided games (SSG) using different ratios of players to pitch area (densities) in soccer players. Methods: A total of 19 professional soccer players from the same soccer club (age = 17.1 [0.3] y, height = 1.76 [0.69] m, and body mass = 69.7 [9.4] kg) participated in this study. Players performed 4 × 30-s (150 s recovery) all-out 1-vs-1 SSG considering 300, 200, and 100 m2 per player (48 h apart). Players’ external l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 28 publications
3
31
1
Order By: Relevance
“…In comparison, the players in the current study covered only 61% of the distance at speeds below 13 km/h, indicating a clearly higher intensity, which in turn explains the greater ØHR and BLC (Table 1). BLC at a similar level as in the current study (11.4 ± 3.31 mmol L −1 ) has been reported by Castagna et al [32] in repeated bouts (4 × 30 s with 150 s recovery) of 1 vs. 1 SSGs with mini-goals (1.5 × 2 m) played on a relatively large pitch (30 × 20 m). The SSGs were performed allout; ergo, the players were told to cover as much distance as possible to create maximal effort (RPE, 8 ± 1).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In comparison, the players in the current study covered only 61% of the distance at speeds below 13 km/h, indicating a clearly higher intensity, which in turn explains the greater ØHR and BLC (Table 1). BLC at a similar level as in the current study (11.4 ± 3.31 mmol L −1 ) has been reported by Castagna et al [32] in repeated bouts (4 × 30 s with 150 s recovery) of 1 vs. 1 SSGs with mini-goals (1.5 × 2 m) played on a relatively large pitch (30 × 20 m). The SSGs were performed allout; ergo, the players were told to cover as much distance as possible to create maximal effort (RPE, 8 ± 1).…”
Section: Discussionsupporting
confidence: 91%
“…Given the fact that all available studies on SSGs reported clearly lower values for BLC, the current study's chosen load protocol appears to be particularly suited to provoke a very high BLC in a soccer-specific test situation. Thus, this also enables the evaluation of players' anaerobic capacity that is an important precondition to cope with high-intensity phases during matches more frequently and for longer periods of time [32]. All things considered, the SSG protocol utilized in the present study caused a very high internal load for the players involved.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…For the aims of this study, the interchangeability of GPS and MCIS for TD, HIRD, TSD, Acc/ Dec and P met needed to be calculated as first step. A 10Hz GPS (K-Sport, Montelabbate, Italy) unit was used to collect data during the training sessions [30]. The GPS unit was placed within a dedicated pouch between the player's shoulder blades (upper thoracic-spine) in a sports vest and worn under the playing jersey.…”
Section: Methodsmentioning
confidence: 99%
“…For the aims of this study, the interchangeability of GPS and MCIS for TD, HIRD, TSD, MechW and P met needed to be calculated as first step. A 10Hz GPS (K-Sport, Montelabbate, Italy) unit was used to collect data during the training sessions [18]. The GPS unit was placed within a dedicated pouch between the player’s shoulder blades (upper thoracic-spine) in a sports vest and worn under the playing jersey.…”
Section: Methodsmentioning
confidence: 99%